FORMATION OF SOCIAL MOTIVE IN PRIMARY CLASS STUDENTS - AS A PEDAGOGICAL PROBLEM - Murod KHOLYIROV (Scholar Express Journal, 2023)
In this article, the factors related to the formation of social motives of elementary school students of general secondary education are highlighted, and this article is intended for a wide audience.
Keywords: ability; need; reflection; motive